Conference on Future Automotive Technology Focus Electro Mobility - Lienkamp, Markus; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2013)
The increasing trend towards electric cars leads to several challenges for the automobile industry, research institutes and politics as well as for the society. Research and serial development move closer together to meet automotive standards with new components such as traction batteries integrated into hybrid and electrical drivetrains. Furthermore, the influence of e-mobility on the daily mobility behavior, the effects on the automotive supply chain and the impact on industrial production have to be taken into account. According to these complex aspects it is crucial to not only acquire specific knowledge in the particular fields but also to consider their functional interaction. Therefore, it seems essential to merge competence from science, economy and politics. This year, the annual „Conference on Future Automotive Technology“ as the follow-up of the „2. Automobiltechnisches Kolloquium München” focuses on the economical realization of widespread automotive electro mobility. Contents - Energy Storage Technologies - Mobility and Service - Powertrain - Vehicle Concepts   Target Groups Academics from engineering and practitioners from automotive industry with interest in electro mobility.   About the Editor Prof. Lienkamp is Director of Research at TUM’s Munich School of Engineering, the Science Center for Electro Mobility, the CREATE project in Singapore and the Ordinarius of the Institute of Automotive Technology at the TU Munich.  .
Energy Storage Technologies -- Mobility and Service -- Powertrain -- Vehicle Concepts and Engineering.
Keywords: Energy systems; Automotive engineering; Energy Systems; Automotive Engineering